The Production of Chitosan from Shrimp Shell Waste and Its Formulation in Patch DosageForm Combined with Aloe vera Extract as Antiinfection Agent - Haeriah, Haeriah; Rahmatullah, Muhammad; Indardaya, Andi; Utomo, Emilia; Novianti, Novianti; Sartini, Sartini (Hasanuddin University, 2017)
Chitosan can be obtained from chitin isolated from shrimp waste through the process of deacetylation of chitin. Chitosan can be used as a patch base material because of its biocompatibility and biodegradability, and has antibacterial activity. The combination of Chitosan and Aloe vera extracts may be useful in patch dosage forms as wound dressings that have antiinfective activity. The research methods was laboratory experimental which consists of : chitosan was obtained from shell waste sequentially by deproteinisation, demineralisation, and deacetylation processes, and analyzed its characteristic, respectivel; Aloe vera gel was extraction by maceration methods using ethanol as solvent; patches were formulated using 2 % chitosan in 1.5 % glacial acetic acid, 1.6 % Aloe vera extracts and 10 % glycerin and evaluated its physical propoperties, skin iritation test, and antibacterial test against S.aureus. The results showed that percentage yield of chitosan was 32.67%, with characteristics; Its viscosity 93.33 cps, pH 4, 30 % deacetylation degree. Percentage yield of Aloe vera extract was 22.73%, containing acemannan, and had antibacterial activity against S.aureus. The result of patch evaluation showed that the thickness of patch was 0.45 mm, 114 times folding endurance, moisture uptake of 45.03%, moisture content of 23.64%, safe to use, and diameter of inhibition zone was 6.39 mm against S.aureus. So, combination of Aloe vera and Chitosan from shrimp shell as patch may use as antiinfection wound healing. Keywords : Aloe vera L.; chitosan; wound dressing; patch; shrimp shell waste